Reviews. (1st December 2016) - Boudraa, Nabil; Martinon, Jean-Paul; Miraglia, Anne Marie; Miraglia, Anne Marie; Oktapoda, Efstratia; Oktapoda, Efstratia
We Are Imazighen: The Development of Algerian Berber Identity in Twentieth-Century Literature and Culture, Fazia Aitel (2014) Gainseville: University Press of Florida, 324 pp., ISBN-10: 0813049393, h/bk, 74.95La Transmission littéraire et cinématographique du génocide des Tutsi au Rwanda, Virginie Brinker (2015) Paris: Classiques Garnier, 481 pp., ISBN: 9782812432545, p/bk, £44.48Littératures québécoise et acadienne contemporaines au prisme de la ville, Anne-Yvonne Julien and André Magord (2014) Rennes: Presses Universitaires de Rennes, 528 pp., ISBN: 9782753532892, p/bk, 24 €A Practical Guide to French Harki Literature, Keith Moser (ed.) (2014) Lanham: Lexington Books, xv + 256 pp., ISBN: 9780739190098, h/bk, 90.00 (£60.00)Francographies: Identité et altérité dans les espaces francophones européens, Bainbrigge Susan, Joy Charnley et Caroline Verdier (éd.) (2010) New York: Peter lang Publishing, 418 pp., ISBN: 9781433103483, h/bkAimé Césaire à l'oeuvre, Cheymol Marc et Philippe Ollé-Laprune (2010) Paris: Éditions des archives contemporaines, Agence Universitaire de la Francophonie (AUF), 270 pp., ISBN: 9782813000408, p/bk, €34.00